Effects of isoleucine on glucose uptake through the enhancement of muscular membrane concentrations of GLUT1 and GLUT4 and intestinal membrane concentrations of Na+/glucose co-transporter 1 (SGLT-1) and GLUT2. Issue 4 (20th June 2016) - Zhang, Shihai; Yang, Qing; Ren, Man; Qiao, Shiyan; He, Pingli; Li, Defa; Zeng, Xiangfang
Abstract: Knowledge of regulation of glucose transport contributes to our understanding of whole-body glucose homoeostasis and human metabolic diseases. Isoleucine has been reported to participate in regulation of glucose levels in many studies; therefore, this study was designed to examine the effect of isoleucine on intestinal and muscular GLUT expressions. In an animal experiment, muscular GLUT and intestinal GLUT were determined in weaning pigs fed control or isoleucine-supplemented diets. Supplementation of isoleucine in the diet significantly increased piglet average daily gain, enhanced GLUT1 expression in red muscle and GLUT4 expression in red muscle, white muscle and intermediate muscle ( P <0·05). In additional, expressions of Na + /glucose co-transporter 1 and GLUT2 were up-regulated in the small intestine when pigs were fed isoleucine-supplemented diets ( P <0·05). C2C12 cells were used to examine the expressions of muscular GLUT and glucose uptake in vitro . In C2C12 cells supplemented with isoleucine in the medium, cellular 2-deoxyglucose uptake was increased ( P <0·05) through enhancement of the expressions of GLUT4 and GLUT1 ( P <0·05). The effect of isoleucine was greater than that of leucine on glucose uptake ( P <0·05). Compared with newborn piglets, 35-d-old piglets have comparatively higher GLUT4, GLUT2 and GLUT5 expressions. The results of this study demonstrated that isoleucine supplementation enhanced the intestinal and muscular GLUT expressions, which have important implications that suggest that isoleucine could potentially increase muscle growth and intestinal development by enhancing local glucose uptake in animals and human beings.